Mindfulness‐based stress reduction for older adults with worry symptoms and co‐occurring cognitive dysfunction. (18th February 2014) - Lenze, Eric J.; Hickman, Steven; Hershey, Tamara; Wendleton, Leah; Ly, Khanh; Dixon, David; Doré, Peter; Wetherell, Julie Loebach
<x xml:space="preserve">Abstract</x> Background Mindfulness‐based stress reduction (MBSR) has the potential to reduce worry and improve cognitive functioning. Objectives In this treatment development project, we examined MBSR in older adults with worry symptoms and co‐occurring cognitive dysfunction. We examined (i) acceptability of MBSR, (ii) whether MBSR needs to be lengthened providing more repetition, (iii) MBSR's benefits for worry reduction and cognitive improvements, and (iv) continued use of MBSR techniques during follow‐up. Methods Two sites (St. Louis and San Diego) enrolled individuals aged 65 years or older with significant anxiety‐related distress plus subjective cognitive dysfunction, into traditional 8‐session MBSR groups and 12‐session groups that had the same content but more repetition of topics and techniques. We examined measures of mindfulness, worry, and a neuropsychological battery focused on memory and executive function before and after the MBSR program, and we followed up participants for 6 months after the completion of MBSR regarding their continued use of its techniques. Results Participants (N = 34) showed improvements in worry severity, increases in mindfulness, and improvements in memory as measured by paragraph learning and recall after a delay, all with a large effect size. Most participants continued to use MBSR techniques for 6 months post‐instruction and found them helpful in stressful situations. There was no evidence that the extended 12‐week MBSR produced superior cognitive or clinical outcomes, greater satisfaction, or greater continuation of MBSR techniques than 8‐week MBSR. Conclusions These preliminary findings are promising for the further testing and use of MBSR in older adults suffering from clinical worry symptoms and co‐occurring cognitive dysfunction. These are common problems in a broad range of older adults, many of whom have anxiety and mood disorders; therefore, stress reduction intervention for them may have great public health value. Copyright © 2014 John Wiley & Sons, Ltd.